2022
DOI: 10.3390/mca27010011
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Infective Immigrants on COVID-19 Dynamics

Abstract: The COVID-19 epidemic is an unprecedented and major social and economic challenge worldwide due to the various restrictions. Inflow of infective immigrants have not been given prominence in several mathematical and epidemiological models. To investigate the impact of imported infection on the number of deaths, cumulative infected and cumulative asymptomatic, we formulate a mathematical model with infective immigrants and considering vaccination. The basic reproduction number of the special case of the model wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…In this work, we were interested in studying different vaccination strategies in regard to which groups to vaccinate first. Different mathematical models that include vaccinated people and take into account the efficacy of the vaccine have been developed [64][65][66][67]. For instance, in [65] the authors proposed a stochastic epidemic model, and they found that white noise can result in the extinction of the disease even with a smaller reproduction number.…”
Section: Introductionmentioning
confidence: 99%
“…In this work, we were interested in studying different vaccination strategies in regard to which groups to vaccinate first. Different mathematical models that include vaccinated people and take into account the efficacy of the vaccine have been developed [64][65][66][67]. For instance, in [65] the authors proposed a stochastic epidemic model, and they found that white noise can result in the extinction of the disease even with a smaller reproduction number.…”
Section: Introductionmentioning
confidence: 99%
“…[33] develops a compartmental model to investigate the impact of vaccination coverage on different outcome metrics under the Omicron variant and a less transmissible variant. Importantly, neither work [31,32,33] models and studies screening strategies, which is the main focus of our paper. Specifically, we contribute to this stream of literature by building an extended compartmental model to study routine screening strategies, which may be customized based on the vaccination status and/or the demographics of campus residents.…”
Section: Introductionmentioning
confidence: 99%
“…The academic literature related to Omicron is still quite limited: [31] develops a compartmental model to predict various outcome metrics related to the Omicron variant under different transmission and severity scenarios, while [32] develops a compartmental model that considers vaccination (including boosters), waning immunity from the vaccine, and different COVID-19 variants (including Omicron), in order to estimate the reduction in transmission rates, and its effect on daily infections, in response to various government policies in Korea. [33] develops a compartmental model to investigate the impact of vaccination coverage on different outcome metrics under the Omicron variant and a less transmissible variant. Importantly, neither work [31, 32, 33] models and studies screening strategies, which is the main focus of our paper.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some countries around the world tightened restrictions on international arrivals to slow the spread of the disease (Gwee et al 2021). Indeed, COVID-19 has slowed economic growth, reduced the number of tourists, as well as technological transfers (Tchoumi et al 2022). Some studies have been conducted on the transmission of COVID-19 in the presence of immigrants.…”
Section: Introductionmentioning
confidence: 99%